The Impact of Network Human Capital on Economic Growth of Supply Chain in Digital Economy - S.A. Dyatlov; Ð¢.Ð. Selishcheva; G.F. Feigin; I.V. Borodushko; D.V. Gilmanov (International Journal of Supply Chain Management, 2018)
Abstract- The article reveals the features of the neural-network technological revolution and digital economy development. They substantiate the proposition that in the modern digital economy new informational-network properties and the competences of highly skilled workers are developed and human capital is transformed into network human capital. The definition of "network human capital" concept is given and its basic properties are revealed. The available methodological approaches are summarized in the economic literature to study the influence of human capital and labor quality on productivity and economic growth of supply chain. They reveal the methodical problems of investment in education quantitative evaluation and their return is determined. They substantiate the thesis that the digital economy has various neuro-network effects from the use of network human capital in the digital neuro-network economy and it is concluded that they need to be evaluated, recorded and included in the gross national product.